Practical guide and spectral atlas for interpretive near-infrared spectroscopy - Workman, Jerry; Weyer, Lois (CRC Press, 2012)
"Interpretive spectroscopy provides a basis for the establishment of cause-and-effect relationships between spectrometer response and the chemical properties of the samples. Without established cause-effect relationships, the measured data will have no true predictive significance. This interpretive process is key for achieving an analytical understanding of the measurement. The popular first edition of this text of this text delivered a unique focus on structure correlation and interpretation of spectra for the practitioner. The thoroughly updated and revised second edition expands on this by offering a full library of four color spectra in a larger format to ensure clarity and reader comprehension"